2019
DOI: 10.1051/e3sconf/201911101075
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Surface Heat Transfer Coefficients of Radiant Systems

Abstract: Heat transfer coefficients are often used to describe the thermal behaviour of radiant systems and how it transfers heat between the cooled/heated surface and the room. In addition to current standards, numerous studies have been conducted to obtain the heat transfer coefficients through experiments and simulations. However, inconsistency is evident in the values or expressions suggested. Thus, this study investigated possible sources of discrepancy through an extensive literature review on articles and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…To quantify the impact of air circulators on the cooling capacity, convective heat transfer needs to be distinguished from the total cooling capacity. Although many studies on ceiling radiant cooling systems have suggested radiant/convective heat transfer coefficients [1,6,8,[22][23][24], these studies focused on the ceiling radiant cooling system made of top-insulated panels. Thus, heat transfer at the upper panel surface was not considered to determine the radiant/convective heat transfer coefficients.…”
Section: Research Limitationsmentioning
confidence: 99%
“…To quantify the impact of air circulators on the cooling capacity, convective heat transfer needs to be distinguished from the total cooling capacity. Although many studies on ceiling radiant cooling systems have suggested radiant/convective heat transfer coefficients [1,6,8,[22][23][24], these studies focused on the ceiling radiant cooling system made of top-insulated panels. Thus, heat transfer at the upper panel surface was not considered to determine the radiant/convective heat transfer coefficients.…”
Section: Research Limitationsmentioning
confidence: 99%